Specific Interaction With Human Serum Albumin Reduces Ginsenoside Cytotoxicity in Human Umbilical Vein Endothelial Cells - Li, He; Chen, Chen; Li, Zhong-Ming; Yang, Yang; Xing, Chao-Qun; Li, Yang; Jin, Ying-Hua (Frontiers in Pharmacology, 2020)
Human serum albumin (HSA) is an important component of plasma, which has the functions of maintaining colloid osmotic pressure and capillary membrane stability, promoting blood circulation, and anti-oxidation. Three-dimensional structure of HSA determines its ability to bind and transport hormones and other substances. In this study we examined the interactions between HSA and ginsenoside Rg3, Rg5, Rk1, Rh2 and Rh4, which are cytotoxic ginsenosides extracted from red ginseng. Heat transfer generated by the specific interaction between HSA and each ginsenoside was measured using isothermal titration calorimetry (ITC) assay, which demonstrated that all these 5 ginsenosides bound to HSA with binding constants of 3.25, 1.89, 6.04, 2.07 and 5.17×105 M-1, respectively. Molecular docking also displayed that these ginsenosides interact with HSA at different sites of the HSA surface. Importantly, cell viability assay showed that the cytotoxicity of these ginsenosides reduced significantly at the presence of HSA in human vascular endothelial cells (HUVEC). Taken together, this study reveals the mechanism by which these ginsenosides are transported in vivo by not causing damage in vascular endothelium, and also suggests HSA might be an ideal carrier help to transport and execute these ginsenoside functions in human body.